Proteome Adjustments Post Gradual Hypoxic Stress in Barilius bendelisis: Insights into Adaptive Strategies of a Hill Stream Cyprinid - Dewan, Saurabh; Singh, Yashpal; Bhatt, J. P. (Current Proteomics, 2016)
Barilius bendelisis, a small teleost fish inhabiting moderate flowing rivers and spring fed streams with wide Asian distribution is often subjected to environmental and humane perturbations, making it a probable study model for physiological and molecular adaptations to environmental stressors. In the present study, 2D gel electrophoresis and Mass spectrometry based proteomics approach was used to characterize the species responses to gradual and prolonged hypoxia over a period of two months. We observed change in the expression level of 46 protein spots, out of which 31 were upregulated in comparison to normoxic individuals while 15 spots were down-regulated. Applying MS analysis and non-redundant database search 25 of the 46 protein spots that varied were successfully identified, corresponding to about 55% identification rate. Overall compensatory proteome adjustment was directed towards up-regulation of glycolytic pathway, decreased neurotransmission, cytoskeletal reorganization, mitigation of reactive oxygen species and some other stress alleviation responses. However, these findings recapitulate some highly conserved responses towards hypoxia tolerance; the identification of a significant number of proteins in non model fish Barilius bendelisis suggests it may serve as a model for stress proteomics studies and could help to elucidate impact of environmental stressors in fishes and other vertebrates too.
Keywords: two-dimensional gel electrophoresis